Aproximação universidade e sociedade por meio da cultura: reflexões sobre a implantação do centro de convenções da UFSM - Borges, Edison Luiz Pavão (2022)
University institutions have participated more actively in the construction of public policies aimed at the access of the public consumer of culture and art produced and disseminated within universities, with greater investments in cultural equipment, in management, infrastructure and in their own organizational charts arising from the planning and the agenda of institutional policies. In this context, universities, such as UFSM, have the role of developing and inserting in society, social technologies and practices of artistic-cultural production aimed at the development of the communities where they are located (UFSM, 2016). Thus, this study aims to conduct an analysis of Cultural Management and the potential for cultural diffusion of the UFSM Convention Center, as well as its role as an inducer equipment of development and social interaction through culture and art. Moreover, it proposes the verification of the impact of this cultural equipment, in the process of strengthening and approximation between the university and society. This research has a qualitative character, having as instruments of data collection, a documental research and the execution of interviews with managers, cultural producers and cultural consumers. This investigation was characterized as a descriptive research, and under a qualitative approach. It is also classified as a case study. For the data analyses, it was used content analysis based on Bardin (2016) aiming to highlight the findings of the documentary research and the most important and relevant excerpts of the interviews. The results indicate that UFSM has qualified the cultural processes with the effective use of the Convention Center as cultural equipment and with the writing of its Cultural Extension Policy, in addition to promoting itself as a culture diffusing institution and as a potential source of cultural access for the Santa Maria community. Nevertheless, the results also revealed the need for improvement in the processes of communication and relationship with other cultural equipment and deliberative instances of culture at the municipal level, besides the lack of external participation in the internal decision instances. The study presents as a suggestion the implementation of a Cultural Projects Office (GAPCULT) and concludes that it is necessary to enhance the positive points found in the cultural management of UFSM and improve the negative points, in order to effectively promote the relationship of the institution with the society around it, while the processes and cultural cycles are carried out efficiently, promoting interaction between the institution, cultural actors and representatives of the community